Evaluation of tumor recurrence after superselective conventional transcatheter arterial chemoembolization for hepatocellular carcinoma: Comparison of computed tomography and gadoxetate disodium‐enhanced magnetic resonance imaging. Issue 9 (24th February 2016) - Miyayama, Shiro; Yamashiro, Masashi; Nagai, Keiichi; Tohyama, Jun; Kawamura, Kenshi; Yoshida, Miki; Sakuragawa, Naoko
Abstract : Aim: To retrospectively evaluate the detectability of tumor recurrence with computed tomography (CT) and magnetic resonance imaging (MRI) after superselective conventional transcatheter arterial chemoembolization (cTACE) for hepatocellular carcinoma (HCC). Methods: The detectability of tumor recurrence with CT and gadoxetate disodium‐enhanced MRI obtained within 30 days (mean, 16.9 ± 10.1) were compared in 38 patients with recurrent HCC after superselective cTACE. Tumor recurrence was divided into local and distant recurrence. Local recurrence was also divided into intratumoral and peritumoral recurrence. Results: Tumor recurrence (maximum diameter, 19.7 ± 10.1 mm) was demonstrated by images 12.4 ± 11.7 months after cTACE. CT could depict 16 (76.2%) of 21 intratumoral recurrences in 12 patients and 14 (53.8%) of 26 peritumoral recurrences in 11, as well as 39 (55.7%) of 70 distant recurrences in 15 (75%) of 20 patients. Arterial phase MRI could depict 20 (95.2%) of 21 intratumoral recurrences in 14 patients and all 26 (100%) peritumoral recurrences in 21, as well as 60 (85.7%) distant recurrences in all 20 (100%) patients. The detectability of tumor recurrence with MRI was significantly higher than that with CT ( P  = 0.00549). On MRI, pseudolesions were observed in five (13.2%) patients and artifacts in the arterial phase in five (13.2%). Regarding the diagnostic performance, CT was superior to MRI in two (5.3%) patients and MRI was superior to CT in 19 (50%). They were almost equal in 17 (44.7%). Conclusion: The detectability of tumor recurrence after superselective cTACE with gadoxetate disodium‐enhanced MRI was superior to that of CT.